Adsorption chromatography separation of the flavonols kaempferol, quercetin and myricetin using cross‐linked collagen fibre as the stationary phase. (14th November 2012) - Ding, Pingping; Liao, Xuepin; Shi, Bi
Abstract BACKGROUND Kaempferol, quercetin and myricetin are typical flavonols that are most concentrated in many medicinal herbs. However, the separation of these flavonols is very challenging due to their similar molecular structures. In the present investigation, the chromatographic separation of the flavonols kaempferol, quercetin and myricetin was performed using glutaraldehyde cross‐linked collagen fibre (GCF) as the stationary phase. RESULTS Kaempferol, quercetin and myricetin could be completely separated from each other by the GCF column by using gradient elution with different solutions of aqueous ethanol (100% to 70%) and 50% acetone. When the chromatographic separation was carried out at a flow rate of 0.75 bed volume h−1 with a sample loading of 30 mg 7 g−1 GCF, the purity of kaempferol, quercetin and myricetin was 98.17%, 93.81% and 81.76%, respectively. The separation resolution was influenced by column length, flow rate and sample loading amount. The separation efficiency of GCF was not obviously reduced after applications had been repeated five times. In the fifth repeated application, the purity of the recovered kaempferol, quercetin and myricetin was still higher than 97%, 94% and 78%, respectively. CONCLUSION GCF is a promising adsorbent for use as a stationary phase in the chromatographic separation of flavonols from their mixtures. © 2012 Society of Chemical Industry